Computerized tomography and pulmonary diffusing capacity in highly-trained athletes after performing a triathlon. - Caillaud, C.; Serre-Cousine, O.; Anselme, F.; Capdevilla, X.; Prefaut, C. (Journal of Applied Physiology, 1995)
Although heavy exercise is suspected to induce an increase in pulmonary extravascular water, there is no radiographic evidence of interstitial pulmonary edema in athletes after running a long -distance race. The purpose of this study was to investigate the computerized tomographies (CT) of the thorax and the pulmonary diffusing capacity for CO (D L CO) in highly-trained athletes before and after a triathlon (1.5 km swimming, 40 km cycling, 10 km running). Eight male competitors participated in the study. D L CO and alveolar volume (VA) were simultaneously measured during 9 s of breath-holding. The transfer coefficient (KCO = D L CO/VA) was then calculated. CT scanning was performed during breath-holding after complete inspiration with the subjects in the supine position. Scans of 1mm thickness were taken every 10 mm from the lower body of the third thoracic vertebra. Scanner analysis was done by: 1) counting the linear and polygonal opacities (index of interstitial fluid accumulation) and 2) calculating the physical mean lung density (MLD) and the mean slice mass. Scanning slice levels were comparable before and after the race for each subject. Mean time performance was 2:04 +/- 0:32 hr. Results showed a significant reduction in D L CO (44.9 +/- 2.3 vs 42.9 +/- 1.7 ml.min -1 .mmHg -1 p&AMPLT0.05) and KCO (6.0 +/- 0.3 vs 5.6 +/- 0.3 ml.min -1 .mmHg -1 /l of VA, p&AMPLT0.05) 95 min after the triathlon. MLD and slice mass increased in all subjects (0.21 +/- 0.009 vs 0.25 +/- 0.01 g.cm -3 ; p&AMPLT0.0001 for MLD and 1.5 +/- 0.07 vs 1.9 +/- 0.07 for slice mass). In addition, the number of polygonal and linear opacities increased after the race (p&AMPLT0.001). This study confirmed that D L CO and KCO decrease in elite athletes following a long-distance race, indicating an overall reduction in pulmonary diffusing capacity. Consistent with this observation was the concomitant 19% and 21% increase in CT lung density and slice mass, respectively, and the higher number of opacities. These data ? suggest an increase in interstitial fluid after the triathlon.